90 Better conversations: outcomes of an interventional radiology program to develop confident communication in advanced practitioners. (23rd February 2023) - Rose, Emma; Barnacle, Alex; Ho, Anne; Jenkins, Alice
Abstract : Introduction: The Interventional Radiology (IR) team at GOSH includes advanced practitioners (3 radiographers & 1 nurse) who independently perform central venous access, feeding tube changes, oesophageal dilatations and salivary Botox TM injections. The practical competencies have a well-developed training pathway. But the practitioners have felt challenged when developing the skillset required to lead the team in the IR suite, negotiate with anaesthetists/ward doctors and discuss sensitive topics with families. These are skills modelled for and taught to doctors throughout their training, but which may be under-recognised when other healthcare professionals step up and cross boundaries into extended roles. A scenario-based simulation program was designed and delivered to the group to develop these non-operating skills. The aim of this study is to evaluate whether the training improved the practioners' confidence. Methods: A standardised questionnaire was completed by 3 practitioners (2 radiographers, 1 nurse) before the program began and after 18 months of program participation. Practitioners were asked to score their confidence in communicating with families/patients and co-workers/colleagues in a variety of scenarios. They answered 14 questions by scoring 1 (never) to 10 (always). Responses were compared using paired-sample t tests. Results: There was a significant difference in the overall cumulative scores pre-training and post-training (p<0.0001, 95% CI -7.60 - -4.82). A greater difference was seen regarding patient-based scenarios (p<0.0002) than co-worker scenarios (p<0.0014). The scores given by the radiographers showed an extremely significant difference (p<0.0001) compared to the nurse's responses (p=0.1197). Conclusion: The study suggests that scenario-based simulation training can improve the confidence of advanced practitioners in their communication skills.